2016
DOI: 10.1016/j.jep.2016.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of Capparis spinosa root extracts on rat articular pain

Abstract: a b s t r a c tEthnopharmacological relevance: Capparis spinosa L. originates from dry regions of Asia and Mediterranean basin. In traditional medicine of these areas, infusions from caper root are considered to be beneficial for the treatment of rheumatism, gout and against abdominal pains. Aim of the study: To evaluate the pain relieving properties of a Syrian cultivar of Capparis spinosa roots in rat models of osteoarthritis and rheumatoid arthritis. Materials and methods: Decoction (DEC) and hydroalcoholic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…C. spinosa root extracts were reported to relieve pain in complete Freund’s adjuvant (CFA)-induced rheumatoid arthritis and mono-iodoacetate (MIA)-induced osteoarthritis male Sprague-Dawley rats [ 66 ]. It is suggested that the pain reliever effect of C. spinosa roots could be due to the presence of spermidine alkaloids which have anti-inflammatory effects [ 66 ].…”
Section: Pharmacological Effects Of C Spinosamentioning
confidence: 99%
See 1 more Smart Citation
“…C. spinosa root extracts were reported to relieve pain in complete Freund’s adjuvant (CFA)-induced rheumatoid arthritis and mono-iodoacetate (MIA)-induced osteoarthritis male Sprague-Dawley rats [ 66 ]. It is suggested that the pain reliever effect of C. spinosa roots could be due to the presence of spermidine alkaloids which have anti-inflammatory effects [ 66 ].…”
Section: Pharmacological Effects Of C Spinosamentioning
confidence: 99%
“…C. spinosa root extracts were reported to relieve pain in complete Freund’s adjuvant (CFA)-induced rheumatoid arthritis and mono-iodoacetate (MIA)-induced osteoarthritis male Sprague-Dawley rats [ 66 ]. It is suggested that the pain reliever effect of C. spinosa roots could be due to the presence of spermidine alkaloids which have anti-inflammatory effects [ 66 ]. Similarly, the lyophilised methanolic extracts from flowering buds of C. spinosa was also reported to exhibit anti-inflammatory effect by reducing the production of reactive oxygen species (ROS), nitric oxide (NO) and prostaglandins (PGE 2 ) induced by IL-1β on human chondrocytes [ 74 ].…”
Section: Pharmacological Effects Of C Spinosamentioning
confidence: 99%
“…In China, C. spinosa (also named wild watermelon) mainly distributed in Xinjiang Uygur Autonomous Region, which is a kind of sand binding plant and its buds, leaves, roots, and fruits have been used in traditional Uighur Medicine to treat gout and rheumatoid arthritis for a long time [ 8 ]. Recently, many studies have been reported that C. spinosa contains a lot of biochemical compounds including flavonoids, alkaloids, polyphenols, saponins, terpenoids, lectin, essential oils, glycosinolate, and glycosides [ 6 , 9 , 10 , 11 , 12 ], which exhibited a broad range of activities such as anti-inflammatory [ 13 , 14 , 15 , 16 ], anti-viral [ 17 , 18 ], anti-allergeric [ 19 ], anti-arthritic [ 20 ], anti-tumor [ 9 , 17 , 21 ], anti-oxidant [ 22 , 23 , 24 , 25 , 26 ], anti-nociceptive [ 27 , 28 ], anti-diabetic [ 4 , 29 ], anti-hepatotoxic [ 30 ], anti-hyperglycemic [ 31 ], hypolipidemic [ 32 ], and immunomodulatory [ 18 , 33 ]. However, the effect of C. spinosa on the maturation and cytokine production of DCs is still elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Articular damage was induced by injection of CFA (Sigma‐Aldrich) into the tibiotarsal joint . More details are provided in the .…”
Section: Methodsmentioning
confidence: 99%